Criterion validity and test-retest reliability of a physical activity questionnaire in South African primary school-aged children: original research - McVeigh, Joanne; Norris, S. (2012)
Objective: We sought to determine the validity, reliability and ranking ability of an interviewer-administered physical activity questionnaire (PAQ), measuring physical activity (PA) and inactivity history over a 1-week and 1-year period in South African primary school-aged children. Methods: Criterion validity of the PAQ was tested against PA movement counts as measured with an Actical accelerometer in 30 children. Agreement between the two instruments was measured with a weighted Kappa statistic. Test-retest reliability of the past week and past year PAQ was also tested. Results: A positive, significant (r=0.53, p=0.004) relationship was found between total time spent being physically active as measured by the Actical and PAQ. A similar relationship was found for time spent doing sedentary (r=0.63, p<0.001) and vigorous activities (r=0.47, p<0.001), but not for activities of a moderate intensity (r=0.001, p=0.88). The ability of the PAQ to correctly categorise children into activity levels was moderate (κ=0.41, p<0.001). The PAQ was found to be reliable and reproducible with significant (p<0.001) intraclass correlation coefficients for both the past week and past year administrations. Conclusion: The interviewer-administered PAQ is a useful assessment tool in this population of children, as evidenced by its good correlation with Actical measurements. The best application of the questionnaire lies in its ability to qualitatively rank subjects according to activity level.